URGENSI PENDIDIKAN AKHLAK DALAM MEMBENTUK KARAKTER PESERTA DIDIK: Telaah Kritis Konsep Pendidikan dalam Kitab Al-Barzanj? - Noer Rahmah (LP3M IAI Al-Qolam, 2018)
Syaikh Ja'far is one of the leading movers in the field of morals who are consistent towards the youth generation. The medium used is the Book of 'Iqd al-Jaw?hir (gem necklace) better known as al-Barzanj?. In the context of morality of Syaikh Ja'far, there are two main morally individual nature, namely: morals to God, morals to apply simple and grateful, morals towards children and parents, morals against people who did wrong, morals in anger, and; morals in social form, among others: morals in mingle, morals in the profession of work, morals in the family, morals against the weak and the leaders. There are many concepts of moral education in accordance with the concept of character education, because the character is related to moral strength which connotes 'positive' rather than neutral. Thus, the 'character person' is a person who has a positive moral quality, and this should be applicable by using various approaches to produce learners who really have a superior character. Keywords: Moral Education, Character Learners, Book of Al-Barzanj?